Proteomic approaches to decipher cancer cell secretome. (June 2018) - Brandi, Jessica; Manfredi, Marcello; Speziali, Giulia; Gosetti, Fabio; Marengo, Emilio; Cecconi, Daniela
Abstract: In this review, we give an overview of the actual proteomic approaches used in the study of cancer cells secretome. In particular, we describe the proteomic strategies to decipher cancer cell secretome initially focusing on the different aspects of sample preparation. We examine the issues related to the presence of low abundant proteins, the analysis of secreted proteins in the conditioned media with or without the removal of fetal bovine serum and strategies developed to reduce intracellular protein contamination. As regards the identification and quantification of secreted proteins, we described the different proteomic approaches used, i.e. gel-based, MS-based (label-based and label-free), and the antibody and array-based methods, together with some of the most recent applications in the field of cancer research. Moreover, we describe the bioinformatics tools developed for the in silico validation and characterization of cancer cells secretome. We also discuss the most important available tools for protein annotation and for prediction of classical and non-classical secreted proteins. In summary in this review advances, concerns and challenges in the field of cancer secretome analysis are discussed.